O veľkých a maličkých - Čarušin, Jevgenij Ivanovič; Jarin, Peter; Čarušin, Jevgenij Ivanovič (Bratislava : Mladé letá, 1958)
Krátke rozprávočky zo života prírody a deti.
Keywords: ruská literatúra; rozprávky; mladší školský vek